The influence of job experience of the candidates on hotel organization performance / Farah Diyana Ahmad Farrin and Siti Nur Ain Mohd Sani - Ahmad Farrin, Farah Diyana; Mohd Sani, Siti Nur Ain (2017)
This research is to find whether job experience of the candidates affect organization performance. This is also to find that, how much experience of the candidates will be useful to the organization to accept them as an employee of the organization. Besides that, the researcher use descriptive research for research design where we need to describe the research objectives.. The researcher using secondary data as data collecting method. The researcher uses other researcher research paper to support the researcher results and findings Experience of the candidates had gain correlates with the knowledge and skill. Organization performance will improve if the experience that they gain from prior working place relates and be useful for the organization. The studies find that there are positive relations in job experience and organization performance. The related experience that the candidates had gain from prior work place can be useful to current organization.